Strategies to Overcome Customer's Satisfaction to Improve the Quality of Services in Accordance with Banking Ethics: Case Study at Bank DKI, Tanah Abang, Central Jakarta - Helmina Br Ginting (Kusuma Negara Business School, 2021)
Customer service is an approach to customer desired to serve the needs of customers with the aim of increasing customer satisfaction and provide solutions of the unsatisfied costumer. What kinds of complaints, and how to cope with customer complaints in improving the quality of service according to service ethics to increase the satisfied of customer. Resulting in satisfaction for bank our customers and make customers become loyal to the bank. Customer service should be in priority in banking activities. Services performed by a bank employee may take the form of learning more about yourself customers. Also good service done by the bank is knowing what is needed and required by the customer. In gain sympathy customers, banks should be able to give satisfaction to customers. But hope and reality sometimes encountered could cause Gap, namely when the expectation is greater than reality means the customer is not satisfied.